Postprocessing and reliability evaluation of the one-dimensional numerical simulation results in mechanical problems - Wojtas, Jan (Computer Assisted Methods in Engineering and Science, 2019)
This work addresses extended formulation of a new approach proposed to control numerical data error. It  includes developing postprocessing techniques for the approximation of data given in a discrete form and estimation (evaluation) of this data a posteriori error and the reliability index. Theoretical consideration and numerical analysis are based on the adaptive meshless finite difference (MFDM) approach.